ER: the Silk Road of interorganellar communication. (October 2018) - Wang, Jin-Zheng; Dehesh, Katayoon
Highlights: Membrane Contact Sites (MCS) as interfaces for interorganellar communication. MCSs enable differential intracellular lipid distribution. MCSs facilitate Ca 2+ homeostasis, a conserved signaling agent. Abstract : Cellular adaptive responses arise from an array of spatially and temporally distinct biochemical interactions that modulate biological processes and reorganize subcellular structures tailored to the nature of stimulus. As such, cells have evolved elegantly and tightly regulated mechanisms to enable interorganellar communication in part through the dynamic readjustment of physical distance enabling the tethering between two closely apposed membranous organelles and thus formation of Membrane Contact Sites (MCSs). MCSs are dynamic and ubiquitous interorganellar structures that serve as regulatory interfaces to facilitate transmission of signals and to integrate synthesis of metabolic pathways such as lipids required for upholding cellular homeostasis in response to environmental and developmental inputs. Endoplasmic reticulum (ER) is the most copious endomembrane system that extend throughout the cell, and functions in production, processing, and transport of proteins and lipids, as well as in intracellular signaling. Reminiscent of the ancient Silk Road, ER connection to other membranous organelles via MCSs alters cellular landscape and serves as nexus for coordinating exchange of metabolites such as lipids, ions such as Ca 2+, and other small molecules involved in maintaining cellular integrity under prevailing conditions. Delineating the molecular organization of the tethering complexes, molecular action of exchanged molecules and hence the nature of information transmitted will afford insight into underlying basis of interorganellar communication and shed light on the evolutionarily conserved function of ER as the ancient trans-kingdom Silk Road trafficking vital metabolites via the non-vesicular pathway.